1973
DOI: 10.1021/jo00960a015
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyalthioacrylates

Abstract: for the microanalyses, Dr. T. Williams for the nmr spectra, Mr. S. Traiman for the ir spectra, Dr. W.Benz for the mass spectra, and Dr. V. Toome for the uv spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…For many decadest he reactivity of electron deficient acetylenes with thiols hasb een explored both in organic [68][69][70] and Scheme17. Application of diarylthiomaleimidesint he generation of peptideconjugates for therapy and study of biological systems.…”
Section: Arylpropionitrilesmentioning
confidence: 99%
“…For many decadest he reactivity of electron deficient acetylenes with thiols hasb een explored both in organic [68][69][70] and Scheme17. Application of diarylthiomaleimidesint he generation of peptideconjugates for therapy and study of biological systems.…”
Section: Arylpropionitrilesmentioning
confidence: 99%
“…[6] Application of this method to step-growth polymerization has allowed us to access high molar mass polymers with control over double bond stereochemistry,m onomer composition, and chain-end functionality to create elastomeric materials with independently tuneable mechanical and physical properties.…”
mentioning
confidence: 99%
“…[4] Combination of the control over degree of crystallinity and mechanical properties through backbone double-bond stereochemistry,a se xemplified by natural rubber/gutta percha, with the tunability of materials properties of synthetic materials via monomer selection and end group modification, presents an ew method by which to undertake the rational design of elastomers and presents an entire new design space for functional materials.Acritical deficiencyofsynthetic methods in the ability to control double-bond stereochemistry using monomers with diverse functional groups limits the development of novel materials that mimic the method of mechanical property control exemplified in natural rubber and gutta percha elastomers.T he application of click chemistry,r eactions that are so categorized because of their modular nature,s ingle reaction trajectory,equimolarity,high yields,simple purification, chemoselectivity,and fast timescales, [5] could potentially address the synthetic pitfalls and afford access to high-molarmass polymers with defined stereochemistry.Indeed, we and others have recently demonstrated that the organobasecatalyzed addition of thiols to activated alkynes could be stopped after asingle addition and furthermore,byjudicious choice of catalyst or solvent polarity,t he stereochemistry of the resultant alkene could be controlled. [6] Application of this method to step-growth polymerization has allowed us to access high molar mass polymers with control over double bond stereochemistry,m onomer composition, and chain-end [*] Dr.…”
mentioning
confidence: 99%